2005
DOI: 10.1155/2005/763421
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic Changes in Mitochondrial Membrane Potential (Δψm) during Valinomycin‐Induced Depolarisation and Apoptosis

Abstract: A large body of evidence has implicated mitochondria in control of cell death, where key apoptotic mechanisms involve change in mitochondrial membrane permeability and depolarisation of mitochondrial membrane potential (Δψm). Assessment of Δψm is traditionally conducted using the lipophilic cation JC-1 on the flow cytometer or by fluorescent microscopy. Here we assess JC-1 aggregation using the novel tool of digital texture analysis to establish mitochondrial phenotypic changes induced by the K+ ionophore, val… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
4
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 8 publications
1
4
0
Order By: Relevance
“…As the exposure time was extended, ▵Ψm showed a trend of rising initially and then falling. Previous research considered that external chemicals would decrease ▵Ψm and induce apoptosis of cells (Morrison et al 2016;Wu et al 2020). Similarly, a reduced ▵Ψm appeared in the 100-mg/L nitrite exposure group at 24 h in the present study; however, this reduction was not observed in the other nitrite exposure groups.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…As the exposure time was extended, ▵Ψm showed a trend of rising initially and then falling. Previous research considered that external chemicals would decrease ▵Ψm and induce apoptosis of cells (Morrison et al 2016;Wu et al 2020). Similarly, a reduced ▵Ψm appeared in the 100-mg/L nitrite exposure group at 24 h in the present study; however, this reduction was not observed in the other nitrite exposure groups.…”
Section: Discussionsupporting
confidence: 55%
“…Previous research considered that external chemicals would decrease ▵Ψm and induce apoptosis of cells (Morrison et al. 2016; Wu et al. 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Although these mechanistic aspects are under investigation, flow cytometry experiments run on MCF-7 cells stained with the mitochondria-specific fluorescent probe JC-1 indicate that HyVLMs, similarly to VLM, induce ΔΨ m dissipation, an event that is known to precede the VLM-triggered apoptosis. ,, In particular, we found that the percentage of JC-1-loaded MCF-7 cells with depolarized mitochondria, upon exposure to compounds 1 – 4 for 72 h, were 16, 8.9, 12.1, and 15.6%, respectively, as opposed to a 1% of MCF-7 control cells. It is noteworthy that these percent values strictly parallel the order of cytotoxicity of compounds 1 – 4 (IC 50 values of Table 1), as well as their relative order of efficiency ( 1 > 3 ≈ 4 > 2 ) in depolarizing isolated rat-liver mitochondria …”
mentioning
confidence: 73%
“…To highlight the antiproliferative activity of compounds 1 – 4 , we evaluate their ability to interfere with the cells cycle progression of MCF-7 cells by flow cytometry. It is well-known that VLM is a potent apoptotic inducer. ,, However, in our preliminary experiments, cells treated with compounds 1 – 4 showed only a marked accumulation in S phase after 24 h of incubation, irrespective to the utilized concentrations (Figure ; Table S1, Supporting Information). As already suggested by Iguchi et al, an accumulation in S phase could be correlated to apoptosis through the modulation of MAPK and mevalonate pathways. , After 72 h of incubation, only VLM showed a marked accumulation of cells in the G2/M phase, which might be compatible with an induction of apoptosis.…”
mentioning
confidence: 73%
See 1 more Smart Citation